Therapy Processes Associated With Sudden Gains in Cognitive Therapy for Depression: Exploring Therapeutic Changes in the Sessions Surrounding the Gains - Lemmens, Lotte H. J. M.; DeRubeis, Robert J.; Tang, Tony Z.; Schulte-Strathaus, Julia C. C.; Huibers, Marcus J. H. (Frontiers in Psychiatry, 2021)
Background: The frequency and clinical impact of Sudden Gains – large symptom improvements during a single between-session interval – in psychotherapy for depression have been well established. However, there have been relatively few efforts to identify the processes that lead to sudden gains. Aim: To explore therapy processes associated with sudden gains in cognitive therapy for depression by examining changes in the sessions surrounding the gains, and the session preceding the gain in particular. Methods: Using ratings of video-recordings (n=36), we assessed the content, frequency and magnitude of within-session cognitive-, behavioural-, and interpersonal change, as well as the quality of the therapeutic alliance in the session prior to the gain (pre-gain session), the session after the gain (post-gain session) and a control session. After that, we contrasted scores in the pre-gain session with those in the control session. In addition, we examined changes that occurred between the pre- and post-gain session (between-session changes) and explored patients’ attributions of change. Results: Although not statistically significant, within-session changes were more frequent and stronger in the pre-gain session compared to the control session. The largest difference between the pre-gain and control session was found in the behavioural domain, and reached the level of trend-significance. There were more, and more impactful between-session changes in the interval during which the gain occurred as compared to a control interval. Exploratory analysis of attributions of change revealed eight subcategories, all corresponding with the cognitive-, behavioural- and interpersonal- domain. The quality of the therapeutic alliance was high and almost identical in all sessions. Conclusion: In spite of its small sample size, our study provides relevant descriptive information about potential precipitants of, themes related to, and attributions given for sudden gains. Furthermore, our study provides clear suggestions for future research. A better understanding of session content in the sessions surrounding sudden gains may provide insight into the mechanisms of change in psychotherapy, hereby suggesting treatment-enhancing strategies. We encourage researchers to conduct research that could clarify the nature of these mechanisms, and believe the methods used in this study could serve as a framework for further work in this area.